Equine Transport and Changes in Equid Herpesvirus' Status - Muscat, Katharine E.; Padalino, Barbara; Hartley, Carol A.; Ficorilli, Nino; Celi, Pietro; Knight, Peter; Raidal, Sharanne; Gilkerson, James R.; Muscatello, Gary (Frontiers in Veterinary Science, 2018)
The risk of respiratory disease in the transported horse can increase as a consequence of immunosuppression and stress associated primarily with opportunistic bacterial proliferation and viral reactivation. This study examines the ecology of equid herpesviruses (EHV) in these horses, exploring reactivation and changes in infection and shedding associated with transport, and any potential contributions to transport-related respiratory disease. Twelve horses were subjected to an 8-hour road-transport event. Antibodies to EHV-1 and EHV-4 were detected by ELISA in serum collected prior to, immediately after and 2 weeks post transport. Respiratory tract endoscopy and tracheal washes were collected prior to and 5 days after transportation. Nasal swabs collected prior to, immediately after, 1 day and 5 days following transport were screened for EHV-1,-2,-4,-5 using qPCR. Six horses had persistent neutrophilic airway infiltrates post transportation, indicative of subclinical respiratory disease. No horses were qPCR positive for either of the alphaherpesviruses (i.e. EHV-1/-4) nor did any seroconvert to either virus. Four out of nine horses positive for either EHV-2 or EHV-5 on qPCR prior to transport developed neutrophilic airway inflammation. Five horses showed increasingly positive readings on qPCR (i.e. reduced Cq) for EHV-2 after transportation and seven out of eleven horses positive for EHV-2 after transport shared strains of high sequence similarity with other horses in the study. One EHV-2 virus detected in one horse after transport was genetically different which may be due to reactivation. The clinical significance of EHV-2 and EHV-5 remains in question. However these results indicate that transportation may lead to increased shedding, transmission and reactivation of EHV-2 and EHV-5 but not EHV-1/-4. Unlike previous work focusing on the role of alphaherpesviruses, this research suggests that investigation of the gammaherpesviruses (i.e. EHV-2/-5) in transport-related disease should not be dismissed, particularly given that these viruses can encode suppressive immunomodulators that may affect host health.